The correlation between Mother's Knowledge About Language Stimulation and Language Development Of Toddlers in Lengkong, Mumbulsari, Jember - Mardhiyyah Nurul Hasanah; Dwita Aryadina Rachmawati; Erfan Efendi (Faculty of Medicine, University of Jember, 2019)
Abstract The first three years of age is an important period for the development of children’s languange. Early stimulation as a parent especially mother to promote children’s development needs to be done. Before doing stimulation, the mothers need sufficient knowledge about development stimulation so mothers can do stimulation properly to their children. The aim of this study is to analyze the correlation between the mother’s knowledge about language stimulation and language development of toddlers in Lengkong , Mumbulsari, Jember. An analitic observational study with cross sectional study design which the subjects were 70 mother who have toddlers at Lengkong, Mumbulsari, Jember who met inclusion and exclusion criteria. The result of spearman correlation test between mother’s knowledge about language stimulation and language development of children aged 1-3 years is p=0,000 (p<0.005) which mean there is significant correlation between the mother’s knowledge about language stimulation and language development of children aged 1-3 years in Lengkong , Mumbulsari, Jember. Keywords: knowledge, stimulation, language development.